2013
DOI: 10.1155/2013/532850
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Activity of Upper Thoracic Dorsal Root Ganglion Neurons in Zucker Diabetic Fatty Rats

Abstract: The aim of the present study was to examine the calcium activity of C8-T5 dorsal root ganglion (DRG) neurons from Zucker diabetic fatty rats. In total, 8 diabetic ZDF fatty animals and 8 age-matched control ZDF lean rats were employed in the study. C8-T5 dorsal root ganglia were isolated bilaterally from 14 to 18 weeks old rats, and a primary culture was prepared. Calcium activity was measured ratiometrically using the fluorescent Ca2+-indicator Fura-2 acetoxymethyl ester. All neurons were stimulated twice wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It has been shown that mitochondrial dysfunction in sensory neurons from type 1 diabetic rats is related to impaired rates of respiratory activity [17], and impaired respiratory function is associated with reduced ROS generation in the mitochondrial matrix of cultured DRG neurons isolated from STZ-diabetic rats [16]. Alterations in calcium activity have been found in DRGs from Zucker Diabetic Fatty Rats [54]. Our study and the related previous studies show that the diabetes induces many effects on peripheral neurons in diabetic animal models [55].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that mitochondrial dysfunction in sensory neurons from type 1 diabetic rats is related to impaired rates of respiratory activity [17], and impaired respiratory function is associated with reduced ROS generation in the mitochondrial matrix of cultured DRG neurons isolated from STZ-diabetic rats [16]. Alterations in calcium activity have been found in DRGs from Zucker Diabetic Fatty Rats [54]. Our study and the related previous studies show that the diabetes induces many effects on peripheral neurons in diabetic animal models [55].…”
Section: Discussionmentioning
confidence: 99%
“…Diminished (in spite of the fact that not generally) and diminished upgrade evoked Ca 2+ signals. Ca 2+ -dealing with disarranges have additionally been found in tangible neurons from creatures with diabetes [11,40,41]. ] I rest was not influenced in neurons from the ganglion in the more elevated levels of the spinal line (C3-L3).…”
Section: Dyshomeostasis Ca 2+ In Neuronsmentioning
confidence: 94%
“…This distinction connects with the lumbar DRG tactile neuron vulnerability and the long axon of diabetic neuropathy. A portion of these distinctions are identified with contrasts in estimation of [Ca 2+ ]I between considers with different models and term of diabetes, maybe likewise because of contrasts in different sub-populaces of neurons from the degree of DRG in the spine [11,40].…”
Section: Dyshomeostasis Ca 2+ In Neuronsmentioning
confidence: 99%